Lymphoepithelial carcinoma of the parotid gland: Clinicopathological analysis of 146 cases from a single institute. Issue 9 (1st August 2022) - Zhang, Chunye; Gu, Ting; Tian, Zhen; Wang, Lizhen; Han, Jing; Hu, Yuhua; Xia, Ronghui; Li, Jiang
Abstract: Background: Parotid lymphoepithelial carcinoma (LEC) is a rare malignant tumor. The purpose of this study was to investigate the clinicopathological features of parotid LEC. Methods: All patients clinicopathological information diagnosed parotid LEC from 2005 to 2017 were analyzed. Results: A total of 146 cases of parotid LECs were identified. Of these, 126 (86.3%) were primary and 20 (13.7%) were secondary LECs. Patients with secondary LEC tended to have tumors with earlier TNM staging than those with primary ( p  = 0.031). The tumor cells in 87 (94.6%, 87/92) cases tested positive for Epstein–Barr virus (EBV). Cervical node metastases were present at diagnosis in 46 (31.5%) cases. Overall survival at 5 and 10 years was 97.0% and 90.8%, respectively. Older age was an adverse prognostic indicator for overall survival ( p  < 0.001). Conclusions: Parotid LEC is associated with EBV and an increased rate of cervical node metastases. However, most patients, especially younger ones, have a good prognosis.